2005
DOI: 10.1532/ijh97.05013
|View full text |Cite
|
Sign up to set email alerts
|

BMI-1 Is Highly Expressed in M0-Subtype Acute Myeloid Leukemia

Abstract: Recent studies have suggested that one of the polycomb group genes, BMI-1, has an important role in the maintenance of normal and leukemic stem cells by repressing the INK4a/ARF locus. Here, we quantitatively examined BMI-1 expression level in samples from patients with acute myeloid leukemia (AML) and other hematologic malignancies. Moderate to high BMI-1 expression was detected in AML patients, and the BMI-1 expression levels in AML samples were significantly higher than in normal bone marrow controls (P = .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 14 publications
4
51
0
Order By: Relevance
“…73 In a separate study, the same group found that such CTL responses were not limited to the immunodominant WT1 [126][127][128][129][130][131][132][133][134] epitope, but could also be directed against other HLA-A*0201-restricted WT1-derived epitopes (WT1 [37][38][39][40][41][42][43][44][45] , WT1 [187][188][189][190][191][192][193][194][195] and WT1 [235][236][237][238][239][240][241][242][243] ). 88 A similar observation was made regarding PRAME, which is known to contain at least four different HLA-A*0201-restricted epitopes that can be naturally recognized (PRA [100][101][102][103][104][105][106][107][108] , PRA 142-151 , PRA 300-309 and PRA [425][426][427][428][429]...…”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 54%
“…73 In a separate study, the same group found that such CTL responses were not limited to the immunodominant WT1 [126][127][128][129][130][131][132][133][134] epitope, but could also be directed against other HLA-A*0201-restricted WT1-derived epitopes (WT1 [37][38][39][40][41][42][43][44][45] , WT1 [187][188][189][190][191][192][193][194][195] and WT1 [235][236][237][238][239][240][241][242][243] ). 88 A similar observation was made regarding PRAME, which is known to contain at least four different HLA-A*0201-restricted epitopes that can be naturally recognized (PRA [100][101][102][103][104][105][106][107][108] , PRA 142-151 , PRA 300-309 and PRA [425][426][427][428][429]...…”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 54%
“…37 Others have also reported that BMI1 expression is elevated in many hematologic malignancies. [38][39][40][41][42] New data may provide some important insights into the possible role of BMI1 in the development of leukemic transformation. In a mouse model in which coexpression of the oncogenes HOXA9 and MEIS1 resulted in a quick onset of myeloid leukemia, no disease was observed in secondary bmi-1-deficient recipients, 12 suggesting that BMI1 is essential for the maintenance of HOXA9-MEIS1 leukemic stem cells.…”
Section: Bmi1-induced Maintenance Of Human Hscs 2627mentioning
confidence: 99%
“…76 Overexpression of PRC1 complex components, such as BMI1, has been correlated with adverse outcomes in several hematopoietic malignancies. [77][78][79][80][81][82] However, little is known about the actual mechanisms involved, but with the advent of genome-wide studies this is likely to change in the near future.…”
Section: H3k27 Methylationmentioning
confidence: 99%